2018
DOI: 10.1038/s41598-017-18216-x
|View full text |Cite|
|
Sign up to set email alerts
|

An assay for the identification of Plasmodium simium infection for diagnosis of zoonotic malaria in the Brazilian Atlantic Forest

Abstract: Zoonotic malaria poses a unique problem for malaria control. Autochthonous cases of human malaria in the Atlantic Forest have recently been attributed to Plasmodium simium, a parasite that commonly infects non-human primates in this Brazilian biome. However, due to its close similarity at both the morphological and molecular level to Plasmodium vivax, the diagnosis of P. simium in this region remains problematic. Therefore, a diagnostic assay able to accurately identify P. simium is important for malaria surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 33 publications
3
49
0
1
Order By: Relevance
“…Following a malaria outbreak in the Atlantic Forest of Rio de Janeiro in 2015/2016, it was shown that these infections were caused by the non-human primate malaria parasite P. simium 1 . DNA samples collected both from humans and non-human primates (NHPs) in the same region shared identical mitochondrial genome sequences, distinct from P. vivax isolates from anywhere in the world and identical to that of a P. simium parasite isolated from a monkey in the same region in 1966, and to all isolates of P. simium recovered from NHPs since 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Following a malaria outbreak in the Atlantic Forest of Rio de Janeiro in 2015/2016, it was shown that these infections were caused by the non-human primate malaria parasite P. simium 1 . DNA samples collected both from humans and non-human primates (NHPs) in the same region shared identical mitochondrial genome sequences, distinct from P. vivax isolates from anywhere in the world and identical to that of a P. simium parasite isolated from a monkey in the same region in 1966, and to all isolates of P. simium recovered from NHPs since 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the 18S rRNA gene, 29 samples were analysed, of which 16 were positive for P. vivax, corresponding to 14 pools of A. K. cruzii collected in tree canopies and two livers from monkey bodies. The proposed protocol to differentiate samples between P. vivax and P. simium (13) were successful for seven samples, six resulting from DNA pools of A. K. cruzii and one from a simian liver.…”
Section: Methodsmentioning
confidence: 99%
“…All DNA samples were tested in triplicate for 18s rRNA Plasmodium genus-specifc gene [29,30], and then for cysteine proteinase P. vivax and ssrRNA P. malariae and P. falciparum genes, as previously described [30,31]. P. vivax- positive samples were submitted to P. simium differential diagnosis based on a mitochondrial SNP [2,10]. The molecular diagnosis was performed by Nested -PCR of coxI gene fragment and subsequent enzymatic digestion, using primers and protocol previously described [10].…”
Section: Methodsmentioning
confidence: 99%
“…P. vivax- positive samples were submitted to P. simium differential diagnosis based on a mitochondrial SNP [2,10]. The molecular diagnosis was performed by Nested -PCR of coxI gene fragment and subsequent enzymatic digestion, using primers and protocol previously described [10]. All the PCR products were visualized under UV light after electrophoresis on 2% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation